Introducing the Strategy for Patient Oriented Research (SPOR) Evidence Alliance: a partnership between researchers, patients and health system decision-makers to support rapid-learning and responsive health systems in Canada and beyond - Andrea C. Tricco; Wasifa Zarin; Fiona Clement; Ahmed M. Abou-Setta; Janet A. Curran; Annie LeBlanc; Linda C Li; Christina Godfrey; Pertice Moffitt; David Moher; Heather Colquhoun; Ian D. Graham; et al. (Canadian Science Publishing, 2022)
This is the introductory paper in a collection of four papers on the Strategy for Patient-Oriented Research (SPOR) Evidence Alliance, a pan-Canadian research initiative that was funded by the Canadian Institutes of Health Research in September of 2017. Here, we introduce the SPOR enterprise in Canada, provide a rationale for the creation of the SPOR Evidence Alliance, provide information on the mandate and approach, and describe how the SPOR Evidence Alliance adds to the health research ecosystem in Canada and beyond.